2020
DOI: 10.1111/pai.13263
|View full text |Cite
|
Sign up to set email alerts
|

Two X‐linked agammaglobulinemia patients develop pneumonia as COVID‐19 manifestation but recover

Abstract: Background:The recent SARS-CoV-2 pandemic, which has recently affected Italy since February 21, constitutes a threat to normal subjects, as the coronavirus disease-19 can manifest with a broad spectrum of clinical phenotypes ranging from asymptomatic cases to pneumonia or even death. There is evidence that older age and several comorbidities can affect the risk to develop severe pneumonia and possibly the need of mechanic ventilation in subjects infected with SARS-CoV-2.Therefore, we evaluated the outcome of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
291
3
9

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(335 citation statements)
references
References 14 publications
12
291
3
9
Order By: Relevance
“…When considered together, these immunomodulatory effects of IVIG products might be beneficial in COVID-19 disease management, but this needs to be confirmed clinically. Although IVIG may not confer protection against SARS-CoV-2, the role of antibodies crossreacting with SARS-Cov-2 has been suggested by exerting a priming effect on host immune response or through an immunomodulatory action on monocytes and tissue-resident macrophages [25]. The antibody-dependent enhancement (ADE) phenomenon associated with non-neutralizing antiviral proteins in IVIG also needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…When considered together, these immunomodulatory effects of IVIG products might be beneficial in COVID-19 disease management, but this needs to be confirmed clinically. Although IVIG may not confer protection against SARS-CoV-2, the role of antibodies crossreacting with SARS-Cov-2 has been suggested by exerting a priming effect on host immune response or through an immunomodulatory action on monocytes and tissue-resident macrophages [25]. The antibody-dependent enhancement (ADE) phenomenon associated with non-neutralizing antiviral proteins in IVIG also needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…75 Both patients developed pneumonia, and both recovered without any need of receiving oxygen therapy. 75 In another Italian study, the clinical course of COVID-19…”
Section: Lessons From Patients With Agammaglobulinemiamentioning
confidence: 93%
“…This hypothesis may contribute to explain why patients with agammaglobulinemia had a mild pneumonia and recovered without experiencing complications requiring oxygen therapy. 75 Antibodies may be simply a consequence of a powerful viral replication, or rather the direct trigger of a severe inflammation. This may be explained with different mechanisms:…”
Section: Triggers Of the Cascades Leading To Ards And Respiratory Fmentioning
confidence: 99%
“…The T cell response was shown to be critical for protection in SARS-1-infected mice [6]. Patients with X-linked agammaglobulinemia, a genetic disorder associated with lack of B cells, have been reported to recover from symptomatic COVID-19 [7,8], suggesting that in some cases T cells are sufficient for viral clearance. Theravajan et al showed that activated CD8+HLA-DR+CD38+ T cells in a mild case of COVID-19 significantly expand following symptom onset, reaching their peak frequency of 12% of CD8+ T cells on day 9 after symptom onset, and contract thereafter [9].…”
Section: Introductionmentioning
confidence: 99%